ANALISIS MANAJEMEN RANTAI PASOK BAWANG GORENG PALU - Nuriyanti, Nuriyanti; Kassa, Saharia; lamusa, Arifuddin (AGROTEKBIS, 2018)
This study aimed to determine the mechanism of supply chain management of Palu fried onions. Itwas research carried out in various places i.e.Soulowe village of Sigi Biromaru subdistrict, Abdul Rahman Saleh street of Palu, Kiranti street of Nunu village of Palu, Wombo Kalonggo village, and Masomba of Palu and conducted during July 2016. Respondents were 23 people consisted of 14onion suppliers, two whole salers, one retailer, three manufacturers, and three customers. Data was analyzed descriptively. The analysis showed that: (1) the structure of the supply chain members werefarmers - traders - industry - retailers/markets - consumer, where each chain has its own function; 2) the flow pattern of the supply chain of Palu fried onions had four channels: product channel flowing from farmers to end consumers, two-way information channel flowing from farmers and such marketing agents as collectors and retailers to consumers, fund channel flowing from consumers to retailers, industry, collector and farmers, and activity channel flowing from farmers to retailers/markets; (3) business partnership that has been well intertwinedwas astrategy for supply chain management of the Palu fried onion.Â Keywords: Palu fried onions, and Supply chainmanagement